Determinan Minat Beli Tiket Bioskop: Perspektif Produk, Harga, Lokasi dan Promosi - Desti Dirnaeni; Christera Kuswahyu Indira; Irfan Ardiansyah (Forum Kerjasama Pendidikan Tinggi (FKPT), 2024)
The aim of this study is to analyze the determinants of purchase intention for tickets to Jungkook's *I AM STILL* documentary. The analytical method used involves primary data, described from quantitative data collected through the distribution of online questionnaires. The tests conducted in this study include validity tests, reliability tests, classical assumption tests, multiple linear regression analysis, partial tests (T-tests), simultaneous tests (F-tests), and determination coefficient (R²). The sampling method employed in this study is purposive sampling, using IBM SPSS Statistics software, with a total sample size of 100 respondents. The T-test results show that the calculated t-values are greater than the critical t-values, as follows: Product (7.871 > 1.985), Price (5.007 > 1.985), Location (5.096 > 1.985), and Promotion (7.871 > 1.985). Thus, it can be concluded that these four independent variables have a partial influence on the purchase intention for tickets to Jungkook's *I AM STILL* documentary. The F-test results indicate that the calculated F-value of 102.326 is greater than the critical F-value of 2.69, meaning that the variables Product, Price, Location, and Promotion simultaneously influence the purchase intention for tickets to Jungkook's *I AM STILL* documentary.